THE EFFECT OF LEVERAGE, INVENTORY TURNOVER RATIO, AND CASH TURNOVER RATIO ON LIQUIDITY WITH PROFITABILITY AS A MODERATING VARIABLE IN TRANSPORTATION AND LOGISTICS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE 2022–2025 PERIOD - Nahzwha Andariesta; Fahmi Natigor Nasution; Firman Syarif (PT. Radja Intercontinental Publishing, 2026)
This study examines the effect of leverage, the inventory turnover ratio, and the cash turnover ratio on liquidity, with profitability positioned as a moderating variable, in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. This issue is important because several logistics firms recorded a Current Ratio below the ideal threshold despite rising revenues, indicating inefficiency in managing short-term financial obligations. Liquidity was measured by the Current Ratio, leverage by the Debt to Equity Ratio, inventory turnover by the Inventory Turnover Ratio, cash turnover by the Cash Turnover Ratio, and profitability by Return on Assets. Using purposive sampling, 25 companies were selected from a population of 39, yielding 100 firm-year observations analyzed through panel data regression and Moderated Regression Analysis (MRA) with EViews 12. The Random Effect Model was chosen as the best estimator based on the Chow and Hausman tests. The results indicate that leverage has a significant negative effect on liquidity, the inventory turnover ratio has a significant positive effect on liquidity, while the cash turnover ratio has no significant effect on liquidity. Profitability significantly moderates the relationship between all three independent variables and liquidity, strengthening the negative effect of leverage and the effect of cash turnover, while weakening the positive effect of inventory turnover.